Analysing teamwork in health care: What matters when clinicians negotiate the continuity of clinical tasks and care responsibilities?. (13th September 2016) - Iedema, Rick; Merrick, Eamon
Abstract : This paper considers the ways in which clinicians enact 'being a team', by analysing how they inform one another about critical patient information. The process where this information exchange happens is known as 'clinical handover'. The study that informs this paper spanned ten months of data collection in four hospitals, involving 150 clinicians and five patients. The analysis presented here draws on data collected at one of the hospital sites: an emergency department at a regional tertiary teaching hospital. Our analysis reveals how central clinical handover is to 'being a team' in health care, and how deficiencies in handover weaken clinical teams' ability to provide continuous and safe care for their patients. We further discuss how clinical practitioners' own responses to the footage foregrounded different issues compared to those revealed by formal analysis; namely, issues centring on relationships, and on practical steps to ensure these relationships could be improved. We reflect on the differences between our own formal analysis of the footage, and practitioners' 'lived response' to the footage, and the implications of these differences for how we as analysts conceptualise 'teamness' in organisations.